Kepemimpinan berbasis Budaya Lokal: Studi pada Budaya Siri' dalam Pembuatan Kebijakan Publik - Muhammad Al Ikhsan; Muhammad Ilham; Prio Teguh (Institut Pemerintahan Dalam Negeri, 2022)
Public skepticism of most of its leaders serves as a driving force behind research. This is because corruption is a serious offense. The executive and legislative branches are where corruption first starts to take place. According to Kartono, a leader who adopts the culture of siri na pacce in himself would develop into a leader who is brave and solid in guiding this research while employing theory (2008:32). This research methodology combines qualitative research with descriptive techniques to describe the condition of the study object based on fieldwork findings. Literature analysis, interviews, documentation, and the use of purposeful approaches in identifying the information are all used as data gathering strategies. According to the findings in the area of decision-making, the mayor makes reference to the laws that are in effect without departing from the culture of Siri. The Mayor declared April 1 to be a day of culture. In terms of motivation, the Makassar City Government employees appreciate one another thanks to the mayor. In order to establish the most impartial justice possible, the government interacts and communicates consciously in Makassar Bugis. The Mayor issued a PERWALI about allegations and unscrupulous conduct in the area of managing subordinates. The Mayor conducted a KASN Recommendation to reinstate previously transferred officials in the area of duty. The Mayor manages emotional control based on the purpose of public service, which is to humanize people